Assessing the severity of laparotomy and partial hepatectomy in male rats-A multimodal approach. - Leonie Zieglowski (Public Library of Science (PLoS), 2021)
This study assessed the postoperative severity after three different visceral surgical interventions in rats by using objective parameters pertaining to various disciplines. The objective was to evaluate whether the degree of severity increases with the invasiveness of the intervention and whether this is in accordance with the EU Directive 2010/63. 136 adult male WistarHan rats were assigned to three groups: Sham-laparotomy (Sham) [7 days post-surgical survival time]; 50% partial hepatectomy (PH); 70% PH [PH groups with 1, 3, or 7 days post-surgical survival times]. Post-surgical severity assessment was performed via several multimodal assessment tools: I) model-specific score sheet focusing on body weight, general condition, spontaneous behavior, and the animals' willingness to move as well as on wound healing; II) Open Field tests evaluating the total distance and velocity an animal moved within 10 minutes and its rearing behavior during the test; III) telemetric data analyzing heart rate and blood pressure; and IV) analysis of blood (AST, ALT, and hemogram) and fecal samples (fecal corticosterone metabolites). Significant differences among the experimental groups and models were observed. We demonstrated that the Open Field test can detect significant changes in severity levels. Sham-laparotomy and removal of 50% of the liver mass were associated with comparable severity (mild-moderate); the severity parameters returned to baseline levels within seven days. Removal of 70% of the liver tissue seemed to be associated with a moderate severity grade and entailed a longer recovery period (>7 days) for complete regeneration. We recommend the use of Open Field tests as part of multimodal objective severity assessment.